The Joint Persona of the Y/BL Couple: Mile/Apo’s Joint Persona within the Adaptation Network - Prasannam, Natthanai; Phumithammarat , Nanphatchaon (Connexion: Journal of Humanities and Social Sciences, 2023)
The purpose of this qualitative study is to investigate the joint persona of the BL couple (also known as the Y couple), Mile/Apo. The research examines media texts generated and disseminated by Be On Cloud Company, focusing specifically on the network of fan/industry interaction and adaptation. Be On Cloud Company implements an innovative business model by establishing the Y/BL series within the Mafia genre and by transforming Mile and Apo into an “adult Y/BL couple.” Three distinct phases comprise the construction of Mile/Apo’s joint persona: prior to, during, and subsequent to KinnPorsche the Series (2022). The joint persona presents a critique of the seme/uke dichotomy by combating androgyny and unbalanced masculinity. Mile/Apo’s portrayal aligns with a Hollywood-popularized bromance trope, which resonates with slash culture among international fans. The research results validate the significance of bromance as an emerging phenomenon in the Thai Y/BL creative sector, in addition to establishing the interconnections between literary texts, media, actors, fans, series directors, and the production company via an adaptation network.